1973
DOI: 10.1071/bi9730491
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypophysectomy on Testicular Hydrolases, Lactate Dehydrogenase, and Spermatogenesis in the Rat

Abstract: Hypophysectomy of the adult male rat depressed testis and seminal vesicle weight between 4 and 8 days after hypophysectomy.The activity of soluble acid proteinase (E.C. 3.4.4.23) and ,B-glucuronidase (E.C. 3.2.1.31) increased between 8 and 16 days after the operation, while that for acid phosphatase (E.C. 3.1.3.2) increased until 16 days after hypophysectomy and then decreased to the end of the experiment.There was an increase in the total acid proteinase and ,B-glucuronidase activity per gram testis between 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Differential distribution of lysosomal enzymes in the testis have been reported. An activity of acid phosphatase was demonstrated in the nuclei of spermatogenic cells (Dempsey -1948) while the activity of beta glucuronidase was observed in Sertoli cells and spermatogonia, and almost none in pachytene spermatocytes (Elkington et al -1973). The activity of acid phosphatase was also localized in the heterogeneous dense granules of the hamster Leydig cells (Yu et al -1977).…”
Section: Discussionmentioning
confidence: 99%
“…Differential distribution of lysosomal enzymes in the testis have been reported. An activity of acid phosphatase was demonstrated in the nuclei of spermatogenic cells (Dempsey -1948) while the activity of beta glucuronidase was observed in Sertoli cells and spermatogonia, and almost none in pachytene spermatocytes (Elkington et al -1973). The activity of acid phosphatase was also localized in the heterogeneous dense granules of the hamster Leydig cells (Yu et al -1977).…”
Section: Discussionmentioning
confidence: 99%
“…, 1969) and its disappearance and reappearance coincide with the cessation and initiation of spermatogenesis during photoperiodically induced testicular involution and recrudescence (Gutierrez et al, 1972). Additionally, LDH-X activity decreases in testes of hypophysectomized rats (Elkington et al, 1972) are similar to the loss of SOX immuno-activity mentioned above.…”
Section: Discussionmentioning
confidence: 61%
“…It has been also observed that acid phosphatase activity is increased in maturing rat testis with a concomitant increase in germinal cells (Males and Turkington -1971). Elkington et al (1973) andrologia 21, No. 4 (1989) reported that hypophysectomy to rats resulted in an elevation in testicular acid phosphatase and P-glucuronidase activities with a concomitant decrease in spermatocyte counts.…”
Section: Discussionmentioning
confidence: 89%